2021
DOI: 10.1186/s12870-021-03075-6
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic responses to drought stress among natural populations provide insights into local adaptation of weeping forsythia

Abstract: Background Understanding the genetic mechanisms of local adaptation is an important emerging topic in molecular ecology and evolutionary biology. Results Here, we identify the physiological changes and differential expression of genes among different weeping forsythia populations under drought stress in common garden experiments. Physiological results showed that HBWZ might have higher drought tolerance among four populations. RNA-seq results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Therefore, the gene expression data in leaves was used for analysis in our study. Previous studies ( Li et al, 2021a , b ) showed that Wuzhishan population has the highest cold and drought tolerance when compared with the other three populations. Thus, the gene expression data of the Wuzhishan population was used as a representative.…”
Section: Methodsmentioning
confidence: 83%
See 1 more Smart Citation
“…Therefore, the gene expression data in leaves was used for analysis in our study. Previous studies ( Li et al, 2021a , b ) showed that Wuzhishan population has the highest cold and drought tolerance when compared with the other three populations. Thus, the gene expression data of the Wuzhishan population was used as a representative.…”
Section: Methodsmentioning
confidence: 83%
“…Expression patterns of the CCD genes in F. suspensa under drought stress were from Wuzhishan population under 80 and 20% soil water content (accession no. SRX7503009 , SRX7503010 , SRX7503012 - SRX7503015 ; Li et al, 2021a ). Expression patterns of the CCD genes in F. suspensa under cold stress were from Wuzhishan populations at 25 and 4°C (accession no.…”
Section: Methodsmentioning
confidence: 99%
“…The gene expression data of weeping forsythia under drought stress were from Wuzhishan populations under 80% and 20% soil water content (accession no. SRX7503009, SRX7503010, SRX7503012-SRX7503015; Li et al 2021b ). The gene expression data of weeping forsythia under cold stress were from Wuzhishan populations at 25 ℃ and 4 ℃ (accession no.…”
Section: Methodsmentioning
confidence: 99%
“…The DEGs of all populations studied largely comprise photosynthesis, oxidation-reduction, and cell membrane component-related genes (Li et al, 2021). Populations of Eucalyptus grandis (Myrtaceae)…”
Section: Transcriptomic Plasticity Drives Differential Drought Responsesmentioning
confidence: 99%